Pengembangan Website Evaluasi Proses dan Hasil Program Layanan Bimbingan dan Konseling - Entis Saefullah; Evi Afiati; Arga Satrio Prabowo (Journal Innovation In Education, 2025)
This research aims to develop the media website sisevprobk.com as a tool for evaluating the process and results of guidance and counseling service programs. This media is designed to assist guidance and counseling teachers in evaluating service programs that have been implemented for students. The research method used is Research and Development (R&D) with the Thiagarajan 4D development model, which includes the stages of definition, design, development and dissemination. The development stage involves product testing with trial participants, namely three guidance and counseling teachers from three schools (SMKN 4 Pandeglang, SMKN 1 Kota Serang, and SMPN 1 Bojong). These teachers are selected randomly and have limitations in evaluating service programs at schools. The data collection technique uses a questionnaire instrument. The trial results showed that the product received a score of 84% in the media and language suitability test, 84% in the material suitability test, and 93% in the usability test by practitioners, with an overall average score of 87%, which is in the "very feasible" category. ". Based on these trials, the website sisevprobk.com was proven to be able to help guidance and counseling teachers in evaluating service programs effectively. Thus, the media website sisevprobk.com is feasible to implement.